A Discrete-Ordinates Solution for the Strong Evaporation Problem in Rarefied Gas Dynamics - Scherer, C. S. (Trends in Computational and Applied Mathematics, 2021)
In this work we solve the nonlinear strong evaporation problem in rarefied gas dynamics. The analysis is based on the BGK model, with three dimensional velocity vector, derived from the Boltzmann equation. We present the complete development of a closed form solution for evaluating density, velocity, temperature perturbations and the heat flux of a gas. Numerical results are presented and discussed.